2012
DOI: 10.1159/000343740
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Differentiation Potentials and Gene Expression Profiles of Mesenchymal Stem Cells Derived from Periodontal Ligament and Wharton’s Jelly of the Umbilical Cord

Abstract: PDLSC-mediated periodontal tissue regeneration is considered a promising method for periodontitis treatment, but the supply of PDLSCs is limited. As a potential alternative, WJCMSCs are readily available; however, there is a lack of evidence proving that WJCMSCs are suitable for periodontal tissue regeneration. In this study, we investigated the characteristics of WJCMSCs and PDLSCs. We found the osteo-/dentinogenic, adipogenic and chondrogenic differentiation potentials of PDLSCs were more powerful than those… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 97 publications
1
38
0
Order By: Relevance
“…However, the osteogenic capacity of WJ-MSCs was significantly lower, as compared to MSCs from other tissue sources. This observation is in agreement with the results of Yu et al [25], reporting that differentiated PDLSCs showed a better mineral deposition as compared to WJ-MSCs, although no significant differences were observed in the upregulation of RUNX2 gene expression in these MSCs. The elevation in RUNX2 mRNA expression indicates the beginning of the ossification process, while in this period no matured osteoblasts can be developed as yet, as suggested by a low level ALP expression, which is an important factor in matrix maturation [26].…”
Section: Discussionsupporting
confidence: 93%
“…However, the osteogenic capacity of WJ-MSCs was significantly lower, as compared to MSCs from other tissue sources. This observation is in agreement with the results of Yu et al [25], reporting that differentiated PDLSCs showed a better mineral deposition as compared to WJ-MSCs, although no significant differences were observed in the upregulation of RUNX2 gene expression in these MSCs. The elevation in RUNX2 mRNA expression indicates the beginning of the ossification process, while in this period no matured osteoblasts can be developed as yet, as suggested by a low level ALP expression, which is an important factor in matrix maturation [26].…”
Section: Discussionsupporting
confidence: 93%
“…MSC differentiation has been a focus of past comparative transcriptome approaches, which has included studies of functional differences in MSC populations (Jansen et al, 2010), characterization of MSC stemness (Gao et al, 2013;Steinert et al, 2015), and assessments of differentiation status (Brown et al, 2015;Granchi et al, 2010;Liu et al, 2014;Menssen et al, 2011;Modder et al, 2012;Satija et al, 2013;Skreti et al, 2014;Steinert et al, 2015;Wislet-Gendebien et al, 2012;Yu et al, 2013;Zhang et al, 2014). For example, temporal and spatial patterns of gene expression profiles were reported for chondrogenic differentiation (Skreti et al, 2014).…”
Section: Tracking Cell Differentiationmentioning
confidence: 99%
“…Then, cells were stained with the Oil Red O working solution for 10 min. The proportion of Oil Red O-positive cells was determined by counting cells under a light microscope [20]. …”
Section: Methodsmentioning
confidence: 99%
“…Cells were visualized under a light microscope, and images were captured for analysis. Blue staining indicated synthesis of proteoglycans by chondrocytes [20]. …”
Section: Methodsmentioning
confidence: 99%